Pre-service Primary Teachers’ Understandings of Inclusive Practice in Scotland and Finland - Mouroutsou, Stella; Koskela, Teija (Aarhus University, 2025)
CONTEXT. Teachers’ attitudes are prerequisite to the implementation of inclusive practices, and teachers’ professional development through their teacher preparation programmes is important for inclusive classroom practice in schools. Developing effective inclusive practice begins in the teachers’ professional preparation. This study investigated pre-service teachers’ understandings of inclusive practice in Scotland and Finland. The aim was to have an in-depth understanding of some pre-service teachers’ views with examples and gain ideas that could count as evidence of inclusive practice, contributing to the dialogue about good inclusive practice.
METHODS. This was a comparative small-scale qualitative study. Data were drawn from focus group interviews with second- and fourth-year pre-service teachers from both countries. The focus groups were conducted online, they lasted around an hour, and they were video and audio recorded. Qualitative data were analysed using thematic analysis. The Finnish data was analysed in Finnish but during the analysis their meanings and interpretations were confirmed through regular discussions.
FINDINGS. In both contexts, the participants understand inclusive education beyond disabilities and special education. There was a better understanding of inclusive practice, more examples and fewer concerns from fourth-year pre-service teachers compared to second-year pre-service teachers. The replies of pre-service teachers in both countries highlighted the importance of values and pedagogy. Pre-service teachers shared examples of pedagogical approaches that they consider to be inclusive, but links to socially-constructed notions of ability or having the same expectations from all pupils were also evident. The findings indicate that a focus on values and pedagogy in both teacher preparation programs is needed with more explicit links between key ideas and practice. It is suggested that the idea of inclusion is embedded in the programs rather than focusing solely on special education modules. This study offers empirical evidence and contributes to inclusive education research, teachers’ professional preparation, policy goals and practice.
KEY MESSAGE. A focus on values and pedagogy in teacher preparation programs is needed with more explicit links between key ideas and practice.